وجوه الخطاب الإصلاحي في تفسير الإمام عبد الحميد بن باديس Faces of the Reformist Discourse in the Quranic Exegesis of Imam Abdelhamid Ibn Badis - (Bey Zekkoub), عبد العالي باي زكوب; (Layth Saud), ليث سعود جاسم (Journal of Islam in Asia (E-ISSN 2289-8077), 2013)
يعدّ عبد الحميد بن باديس أحد العلماء الجزائريين البارزين بالإصلاح الاجتماعي، حيث كان حافزًا له للقيام بتفسير عصريّ لآيات قرآنية مختارة، ملائمة لكل فئات، وطبقات المجتمع الجزائري يومئذ. ولقد فرض الواقع الجزائري المرّ إبّان فترة الاحتلال الفرنسي على ابن باديس سلوكَ سياسة تغيير الخطاب الإسلامي الإصلاحي من حين لآخر قاصدا بذلك مواجهة الاحتلال الفرنسي الغاشم الذي كان يسعى إلى طمس ثوابت الأمّة الجزائرية، وخرق تاريخها، وهُويّتها، وثقافتها، ووحدتها الدينيّة، واللّغوية من خلال عدّة جبهات ومجالات. يهدف هذا البحث إلى استنباط وجوه خطاب الإمام ابن باديس الإصلاحي في التفسير، فيبدأ أوّلاً بالحديث عن مفهوم الخطاب وأهميّته في الإصلاح؛ ثم يتناول بالدراسة والتحليل خطاب ابن باديس الإصلاحي على وجوه رئيسة ستة وهي: الخطاب العقدي، والخطاب الفقهي، والخطاب التهذيبي، والخطاب التذكيري، والخطاب التاريخي، والخطاب الاجتماعي؛ مستعينا بالمنهج الوصفي والتحليلي والاستقرائي. الكلمات المفتاحية: عبد الحميد بن باديس، وجوه الخطاب الإصلاحي، الإصلاح الاجتماعي، الخطاب الإسلامي، الثوابت. *********************** Abdelhamid bin Badis is a prominent Algerian scholar known for his social reformation. He contributed to social reformation by taking up modern interpretation of selected verses of the Qur’an in a way suitable for all types of groups and sections of Algerian society at that time. The bitter Algerian reality during the period of French occupation led Ibn Badis to carry policy of changing Islamic reformist discourse from time to time with intention of confronting brutal French occupation which was attempting to obliterate foundations of Algerian nation; and tearing its history, identity, culture, and religious and linguistic unity, through several fronts and areas. This research aims to excogitate faces of the reformist message of Imam Ibn Badis in his exegesis discusses the concept of the message and its importance in the reform under six main aspects: doctrinal discourse, jurisprudential discourse, ethical discourse, reminder discourse, historical discourse, and social discourse. The research methods applied in the study include descriptive, analytical, and inductive. Key words: Abdelhamid bin Badis, The Faces of the Reformist Discourse, Social Reform, Te Islamic Discourse, Foundations.